FACTORS AFFECTING FRAUDULENT MANAGEMENT OF SCHOOL OPERATIONAL ASSISTANCE (BOS) FUNDS AT PUBLIC HIGH SCHOOLS - Al Amin; Darwanis Darwanis; Fifi Yusmita (JRAK, 2023)
The number of fraud phenomena in Indonesia continues to increase from year to year and occurs in various sectors, including the education sector. This research aims at determining the effect of internal control, accounting information systems, accountability, and transparency on preventing fraud in managing BOS funds. The research was conducted at public high schools in Aceh from July to August 2022, with a population of 380 public high schools and a sample of 296 public high schools in Aceh province. The results showed that internal control, accounting information systems, accountability, and transparency simultaneously influenced fraud prevention in managing BOS funds. To some extent, internal control, accounting information systems, accountability, and transparency are significantly related to fraud prevention in BOS funds management. Therefore, the research implies that it can be used as a benchmark by the management of the BOS fund to prevent any possibility of fraud.